Bibliometrik Analysis of Self Care in Patient with Type 2 Diabetes Mellitus - Murni, Weny; Ernawati (Babali Publisher, 2025)
IntroductionType 2 Diabetes Mellitus is a chronic metabolic disorder with a high global prevalence and a significant risk of complications. The management of this condition heavily relies on effective self-care practices. However, many patients face challenges in implementing self-care due to limited knowledge, inadequate skills, and insufficient social support. The study aimed to employ a Bibliometric analysis to provide a comprehensive overview of the scientific development related to self-care behaviors among patients with Type 2 Diabetes Mellitus. Methods: This study employed a quantitative descriptive method with a bibliometric approach, analyzing scientific publications retrieved from the Scopus database for the period 2021–2025. The search keywords (TITLE-ABS-KEY: